Odpowiedź :
[tex]4. \ (8-4k^{2}+2m^{3}):4 = 2 - k^{2}+0,5m^{3}\\\\5. \ 6cd-2(-c^{2}+3d-5) = 6cd + 2c^{2}-6d+10\\\\6. \ \frac{2(-3+6p)}{3} = 2(-1+2p) = -2+4p\\\\7. \ -3a^{2}+2a(a-4)=-3a^{2}+2a^{2}-8a = -a^{2}-8a[/tex]
(+) · (+) = (+)
(+) · (-) = (-)
(-) · (-) = (+)
Odpowiedź:
1,2,3 dobrze
Szczegółowe wyjaśnienie:
zapisz w ułamku zwykłym
4) 8-4k^+2m 3 /4=
skracam 2 i 4
4-2k^+m 3 /2
5) 2(3cd -(- c^ -3d -5))
2(3cd +c^-3d+5)
-a(3a-2(a-4))
-a(3a-2a+8
-a(a+8)
6) 2*3(-1+2p) /3
2(-1+2p)
-2+4p
7) a*(3a+2(a-4))
a(3a+2a-8)
a(5a-8)